Intimacy across the fencelines : sex, marriage, and the U.S. military in Okinawa - Forgash, Rebecca, 1970- (Cornell University Press, 2020)
"Examines intimate encounters and attachments between U.S. service members and local civilians in Okinawa, Japan, illustrating the intimate effects of militarization on formulations of Okinawan identity, politics, and local U.S. military policy"--